Mapping advocacy and outreach for the Scholarship of Teaching and Learning - Huber, Mary Taylor; Robinson, Jennifer Meta (Teaching and Learning Inquiry, 2016)
From early days, SoTL scholars have documented the “small significant networks” (Roxå and Mårtensson’s term) in which colleagues discuss teaching in local gatherings, as well as in broadly attended conferences and publications. Recent ISSOTL discussions recognize the significance of efforts at this scale and seek to situate them in a larger SoTL landscape, or SoTLscape, of advocacy and outreach activities in the field. In this essay, we present a matrix of possible audiences as an aid to seeing where scholars of teaching and learning are more—and less—active as advocates for SoTL and for positions on pedagogy, curricula, and student success supported by SoTL research. Beyond mapping current activity and looking for gaps, we suggest that the matrix could also help organize pithy accounts of practice into a resource that would stimulate imagination about how scholars of teaching and learning could be more effective as advocates both near to and far from their campus and disciplinary homes.